2019
DOI: 10.1038/s41467-019-09140-x
|View full text |Cite
|
Sign up to set email alerts
|

H3K27M induces defective chromatin spread of PRC2-mediated repressive H3K27me2/me3 and is essential for glioma tumorigenesis

Abstract: Lys-27-Met mutations in histone 3 genes (H3K27M) characterize a subgroup of deadly gliomas and decrease genome-wide H3K27 trimethylation. Here we use primary H3K27M tumor lines and isogenic CRISPR-edited controls to assess H3K27M effects in vitro and in vivo. We find that whereas H3K27me3 and H3K27me2 are normally deposited by PRC2 across broad regions, their deposition is severely reduced in H3.3K27M cells. H3K27me3 is unable to spread from large unmethylated CpG islands, while H3K27me2 can be deposited outsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
286
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(311 citation statements)
references
References 59 publications
23
286
1
1
Order By: Relevance
“…has shown that H3K27M reduces the level of EZH2 automethylation, which decreases PRC2 methyltransferase activity in a manner that most dramatically affects the conversion of H3K27me2 to me3 . This is consistent with the relative effects of H3K27M on H3K27me2 vs. H3K27me3 quantity and deposition .…”
Section: H3k27m Exerts a Dominant Negative Effect On H3k27me3 Throughsupporting
confidence: 67%
See 3 more Smart Citations
“…has shown that H3K27M reduces the level of EZH2 automethylation, which decreases PRC2 methyltransferase activity in a manner that most dramatically affects the conversion of H3K27me2 to me3 . This is consistent with the relative effects of H3K27M on H3K27me2 vs. H3K27me3 quantity and deposition .…”
Section: H3k27m Exerts a Dominant Negative Effect On H3k27me3 Throughsupporting
confidence: 67%
“…The same H3F3A knockdown did not alter survival time of an H3WT paediatric midline HGG. A second study utilized the CRISPR/Cas‐9 methodology in H3.3K27M DIPG xenografts to generate clones completely lacking the H3K27M mutation and compared tumourigenicity of these clones to both an unedited clone and the parental PDX . Here, clones lacking the H3K27M mutation were not able to generate tumours, while both the parental and unedited clones were.…”
Section: Mouse Models Of Dipg and Patient‐derived Dipg Xenografts Promentioning
confidence: 99%
See 2 more Smart Citations
“…making cancer networks distinct from their normal counterparts [27,29,41]. Although conventional tumor genetics categorize mutations into oncogenes and tumor-suppressor genes, recent genetic analyses of gliomas and other malignancies have detected dysregulation of chromatin regulators, which may lead to plasticity in the epigenetic cell state [42][43][44][45]. When analyzed in this context, cancer networks reside at a net higher entropy than do corresponding normal tissues, and display distinct energy relationships between stem and non-stem populations [29].…”
Section: Glossarymentioning
confidence: 99%